Butterworths finance bill ... handbook - Great Britain; Butterworths (Firm) ([London] : Butterworths, 1986)
The provision of this book is relating to income tax, corporation tax, capital gains tax, inheritance tax, value added tax and stamp duty.
gp. 23/01/2019
Loan
Keywords: Taxation; Taxation; Great Britain